An Analysis of the differences in Kitsune imagery between Japanese mythology and the Genshin Impact game - Hastungkoro, Rama Sri; Saifudin, Akhmad (Universitas Dian Nuswantoro, 2024)
This study aims to determine the differences between the depiction of Kitsune in Japanese mythology and the Genshin Impact game, which is depicted by the character Yae Miko. This study uses a descriptive correlational method obtained from the legend of Kitsune (Nine-Tailed Fox) contained in the book Tales of Times Now Past: Sixty-Two Stories from A Medieval Japanese Collection by Maria Ury, which is then compared with the story of Kitsune depicted by the character Yae Miko in the Genshin Impact game. Kitsune is a fox spirit creature that can change its form into a human or a woman. The study found four differences between the depiction of Kitsune according to Japanese mythology and the Genshin Impact game. These differences are in nature, physique, abilities, and hobbies. In Japanese mythology, the figure of Kitsune is depicted as a cunning, manipulative antagonist who often leads humans astray. In contrast, in the game, the protagonist is portrayed as someone who usually helps humans, although his personality changes according to his mood; she does not hurt or kill people. The differences stem from the commodification of online games to attract players. The impact of this difference is the accuracy of the authenticity of Japanese cultural myths, while the positive effect is that Japanese cultural myths can be preserved and widely known throughout the world.